Strict System Equivalence of 2D Linear Discrete State Space Models - Mohamed S. Boudellioua (Journal of Control Science and Engineering)
The connection between the polynomial matrix descriptions (PMDs) of the well-known regular and singular 2D linear discrete state space models is considered. It is shown that the transformation of strict system equivalence in the sense of Fuhrmann provides the basis for this connection. The exact form of the transformation is established for both the regular and singular cases.